2007
DOI: 10.1002/ejic.200600943
|View full text |Cite
|
Sign up to set email alerts
|

Highly Organosoluble Metal‐Free Phthalocyanines and Metallophthalocyanines: Synthesis and Characterization

Abstract: The syntheses and characterization of metal-free and metalcontaining (Zn and Ni) derivatives of a symmetrically octasubstituted phthalocyanine derived from 4,5:12,13-bis(4Ј-tert-butylbenzo) -8,9-(4ЈЈ,5ЈЈ-dicyanobenzo)-6,11-ditosyl-6,11-diaza-2,15-dithiacyclohexadeca-4,8,12-triene and CuPc from 4,5:12,13-bis(4Ј-tert-butylbenzo)-8,9-(4ЈЈ,5ЈЈ-dibromobenzo)-6,11-ditosyl-6,11-diaza-2,15-dithiacyclohexadeca-4,8,12-triene were carried out. Pentanuclear silver(I) and palladium(II) complexes have also been prepared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 43 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Our previous papers have described a series of phthalocyanines with various functional groups. These phthalocyanines have N-, Oand S-containing functionalities such as diazadioxa [25], cryptand [26,27], crown ether fused diloop [28], diazadithia macrocyclic with tert-butyl [29], and tetrathiamonoaza macrocyclic [30]. The immediate consequences of these peripheral substituents are enhanced solubility in common organic solvents and additional donor sites for alkali or transition metal ions.…”
Section: Introductionmentioning
confidence: 98%
“…Our previous papers have described a series of phthalocyanines with various functional groups. These phthalocyanines have N-, Oand S-containing functionalities such as diazadioxa [25], cryptand [26,27], crown ether fused diloop [28], diazadithia macrocyclic with tert-butyl [29], and tetrathiamonoaza macrocyclic [30]. The immediate consequences of these peripheral substituents are enhanced solubility in common organic solvents and additional donor sites for alkali or transition metal ions.…”
Section: Introductionmentioning
confidence: 98%
“…When interacting with strong electromagnetic fields such as laser radiation, the highly conjugated Pc structure promotes preferable polarizability and as well as fast distribution charge. 6 Phthalocyanines are optical limiters that display reverse saturable absorption (RSA). 7,8 This mechanism involves a sequential two photon absorption from the ground state (S 0 ) to a higher excited state (S 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…When peripheral substituents are considered, a condensation reaction with a single phthalonitrile precursor can result in four constitutional isomers with C s , C 2v , C 4h and D 2h symmetries. 6 Symmetry has been found to influence the NLO properties of Pcs. 5 It has been reported that Pcs of lower symmetry show greater optical properties compared to Pcs of higher symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The most important industrial application of phthalocyanines is the formation of color complexes with metal cations that are used as highly stable pigments and dyes [2]. In addition, they can find commercial applications as: photovoltaic materials in solar cells [3e5], systems for fabrication of light emitting diodes (LED) [6,7], liquid crystalline [8], and non-linear optical materials [9,10], sensitizers for photodynamic (PDT) cancer therapy [11,12], photoconductors in xerography [13], dyes at recording layers for CD-R and DVD-R optical storage discs [14], as well as diverse catalytic systems [15,16]. Phthalocyanines are usually prepared by the high temperature cyclotetramerization processes of either phthalonitrile or phthalic anhydride, in which the template effect afforded by a suitable metal cation is required.…”
Section: Introductionmentioning
confidence: 99%